The preminence of ahmad ibn tulun as the leading amir of the Tulunid Kingdom - Jamsari E.A.; Rahman Z.A.; Sulaiman A.; Che Noh N.; Safiai M.H. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus